A surfactant-assisted synthesis of ion-doped and carbon-coated double-modified NVPOF electrode material and preparation method thereof

Through co-precipitation technology and surfactant-assisted synthesis, the NVPOF electrode material that is ion-doped and carbon-coated modified is solved, and the problem of low electron conductivity and slow ion diffusion is achieved, achieving the preparation of high-efficiency and low-cost sodium ion battery positive electrode material and excellent electrochemical performance.

CN118571656BActive Publication Date: 2025-04-04QINGDAO UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410832361.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-04-04
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

The commercial application of existing NVPOF electrode materials in sodium ion batteries is limited by their low electron conductivity and slow ion diffusion kinetics, and traditional synthesis methods such as hydrothermal methods have problems of low yield and high energy consumption.

Method used

Co-precipitation technology combined with surfactant-assisted synthesis is used to perform ion doping and carbon-coated dual modified NVPOF electrode material to form a small disc structure self-assembled from two-dimensional nanosheets along the z-axis to improve the specific surface area and electronic conductivity of the material.

Benefits of technology

By modifying the NVPOF electrode material, the electron conductivity and diffusion rate of sodium ions are significantly improved, the cycle stability and rate performance of the battery are improved, and the synthetic energy consumption and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118571656B_ABST
    Figure CN118571656B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electrode material preparation, and specifically relates to an ion-doped and carbon-coated double-modified NVPOF electrode material synthesized with the assistance of a surfactant and a preparation method thereof. The present invention adopts a coprecipitation technique to synthesize an ion-doped and carbon-coated double-modified NVPOF electrode material assisted by a surfactant. The material is composed of small disks with a diameter of about 1 μm and a thickness of about 200 nm formed by self-assembly of two-dimensional nanosheets along the z-axis. Its unique morphological characteristics can provide a higher specific surface area and more active sites for sodium ion embedding and de-embedding, thereby improving the specific capacity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of electrode material preparation, and in particular relates to an ion-doped and carbon-coated double-modified NVPOF electrode material synthesized with the assistance of a surfactant and a preparation method thereof. Background technology:

[0002] As an emerging energy storage technology, sodium ion batteries have attracted much attention due to their abundant raw materials and low cost. Among them, NVPOF, as a polyanion cathode material for sodium ion batteries with great commercial prospects, has advantages such as high theoretical capacity and stable three-dimensional framework structure, but its inherent low electronic conductivity and slow diffusion kinetics limit the pace of commercial application of NVPOF. At present, the main means of synthesizing NVPOF are divided into hydrothermal method, solvothermal method and coprecipitation method. Among them, the hydrothermal method is a method that is easy to control the morphology and the obtained material has good electrochemical properties, but its yield is low, the reaction time is long, and the energy consumption is high, which makes it difficult to achieve large-scale production. Therefore, the coprecipitation method with good operability and controllability is widely used to obtain NVPOF materials with special structures. During the coprecipitation process, the components are evenly mixed in the solution, which is conducive to obtaining a precipitate with uniform composition and uniform structure. It can ensure that the final sample has good consistency. In addition to the synthesis method, the common modification methods of NVPOF are mainly divided into carbon coating, ion doping, surface modification, structural regulation, etc. Among them, carbon coating improves the surface electron transport properties of NVPOF by coating a layer of conductive carbon material on the surface, significantly improves the electronic conductivity of NVPOF, and thus improves the charge and discharge performance of the battery. However, an overly thick carbon layer will increase the transmission distance of sodium ions in the electrode, which will have an adverse effect on the battery performance. Ion doping effectively improves the crystal structure of NVPOF and increases the diffusion rate of sodium ions by introducing other metal ions into the lattice, thereby improving the cycle stability and rate performance of the battery. However, the selection of doping ions and the optimization of doping amounts are also challenges. Improper doping may lead to a decrease in material performance. Surface modification can form a layer of highly conductive materials (such as metal oxides, conductive polymers, etc.) on the surface of NVPOF, improve the surface electron transport properties, and improve the charge and discharge performance of the battery. However, surface modification may increase the complexity and cost of material preparation. At the same time, the stability and compatibility of the modified materials may also affect the long-term cycle performance of the battery. Structural regulation can increase the specific surface area of ​​NVPOF and increase the diffusion rate of sodium ions by regulating the microstructure of NVPOF, thereby improving the charge and discharge performance of the battery. However, excessive structural regulation may lead to a decrease in the structural stability of the material.

[0003] Therefore, selecting a low-cost, low-energy synthesis method and combining it with appropriate modification methods are key measures to improve the performance of NVPOF and achieve its large-scale preparation. Summary of the invention:

[0004] The technical problem to be solved by the present invention is how to find a low-cost, low-energy consumption synthesis method and combine it with a suitable modification method to improve the performance of NVPOF.

[0005] To solve the above problems, the present invention adopts co-precipitation technology and utilizes surfactant-assisted synthesis of ion-doped and carbon-coated double-modified NVPOF electrode materials. The material is composed of small disks with a diameter of about 1 μm and a thickness of about 200 nm, which are self-assembled by two-dimensional nanosheets along the z-axis. Its unique morphological characteristics can provide a higher specific surface area and more active sites for sodium ion embedding and de-embedding, thereby improving the specific capacity of the material.

[0006] To achieve the above object, the present invention is implemented by the following technical scheme: a method for synthesizing ion-doped and carbon-coated dual-modified NVPOF electrode materials using surfactants, comprising the following steps:

[0007] (1) Dissolve the sodium source, phosphorus source, and fluorine source in deionized water according to the proportion, and stir thoroughly until each drug is completely dissolved to obtain a colorless solution, which is recorded as solution A;

[0008] (2) Take a beaker, dissolve the vanadium source and titanium source in deionized water according to the proportion, and stir thoroughly until all the chemicals are completely dissolved to obtain a blue-white solution, which is recorded as solution B; improve the Na + Diffusion kinetics; In addition, the ion doping strategy was adopted to introduce Ti 4+ Partial replacement of V 4+ . The crystal structure of NVPOF is effectively improved, the diffusion rate of sodium ions is increased, and thus the cycle stability and rate performance of the battery are improved. Dopamine is used as a carbon coating method to form a uniform carbon layer of about 5nm thick on the surface of the sample, which can inhibit the occurrence of secondary crystallization during the sample sintering process and improve its inherent low conductivity problem.

[0009] (3) Transferring solution B to solution A at a certain dropwise addition speed and stirring at a certain rotation speed, a large amount of white-gray floccules are produced at the moment of dropwise addition, and the mixed solution is recorded as solution C;

[0010] (4) After adding surfactant to solution C and stirring thoroughly, the above solution is placed in a water bath and heated in a water bath to obtain a colorless supernatant. The white-gray flocs in the beaker disappear and bluish-white precipitates are produced. Surfactants can reduce the interaction force between NVPOF nanoparticles, help control the growth and aggregation of particles, significantly change the surface energy state of NVPOF nanoparticles, and promote their growth in a specific direction, which can effectively ensure that the final sample has good consistency in both morphology and performance.

[0011] (5) After centrifugation, centrifuge with deionized water and alcohol three times and dry in a drying oven to obtain Na3V 2-x Ti x (PO4)2O2F, Na3V 2-x Ti x POF;

[0012] (6) Na3V 2-x Ti x POF and dopamine hydrochloride were dissolved in tris buffer and stirred thoroughly. The obtained product was centrifuged and washed again and dried. The dried product was calcined in a tube furnace under argon atmosphere to obtain the final product Na3V 2-x Ti x (PO4)2O2F / C, i.e. Na3V 2-x Ti x POF / C. The carbon layer converted from dopamine by carbonization is a nitrogen-doped carbon layer, which can further improve the electronic conductivity of the material.

[0013] During the co-precipitation process, the components are evenly mixed in the solution, which is conducive to obtaining a precipitate with uniform composition and structure. This synthesis method does not require high temperature, has low energy consumption and good controllability, which meets the requirements for industrial-scale electrode material preparation. The obtained samples have the advantages of simple synthesis, low cost, good controllability, uniformity and scalability. As an ideal NASICON-type material in NVPOF, it has the advantages of high operating voltage, stable three-dimensional framework structure, and excellent structural stability. However, its inherent low electronic conductivity and slow ion diffusion rate limit its further application. In addition, based on this, we use surfactant-assisted co-precipitation to obtain ion-doped Na3V at a lower temperature. 2-x Ti x POF materials, by selecting appropriate surfactants, affect the adsorption behavior of the surfactant molecules at the solid-liquid interface, change the interfacial free energy of the material, and guide the NVPOF nanoparticles to grow preferentially along a certain crystal plane, so that a large number of NVPOF nanoparticles grow into a two-dimensional sheet structure. Under the combined action of the appropriate water bath reaction temperature and the concentration of the surfactant, the two-dimensional nanosheet structure will self-assemble and accumulate along the z-axis direction, and finally obtain a micro-nano disc structure. This micro-nano disc structure formed by the self-assembly of two-dimensional nanosheets along the z-axis has a high specific surface area due to its good morphology, which is conducive to the full infiltration of the electrolyte and the provision of more active sites, improving the transfer of electrons at the electrode and solid-liquid interface and optimizing Na +diffusion capacity. Thereby improving the electrochemical performance of the material. In addition to the good morphology that can improve the diffusion kinetics of NVPOF, ion doping is an important means to improve the electrochemical performance of positive electrode materials and is widely used in NVPOF positive electrode materials. The introduction of titanium ions can effectively enhance the electronic intrinsic conductivity of NVPOF, improve its rate performance and reduce the structural deformation and capacity decay during the cycle, thereby extending the service life of the battery. At the same time, carbon coating can further improve the electrochemical performance of positive electrode materials. As a kind of carbon coating method, dopamine has the main advantage that it can self-aggregate on the surface of almost any material, so it can be used to coat most materials, and the carbon layer formed on the surface of the sample can inhibit the occurrence of secondary crystallization during the sintering process of the sample. In addition, the carbon layer converted from dopamine after carbonization is an N-doped carbon layer, which can further improve the electronic conductivity of the material. Finally, by regulating the appearance of NVPOF, a small disc structure formed by the self-assembly of two-dimensional nanosheets along the z-axis is obtained, which is conducive to the rapid transmission of electrons. In addition, its close stacking along the z-axis can also provide a shorter transmission path for sodium ions. This is crucial to improving the inherent low electronic conductivity and slow ion diffusion rate of NVPOF. The NVPOF modified by the above transition metal ion doping combined with carbon coating shows excellent electrochemical performance and shows great potential in the industrialization process of sodium ion battery positive electrode materials.

[0014] Furthermore, the sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium citrate, and sodium fluoride; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and disodium hydrogen phosphate; the fluorine source is one or more of sodium fluoride, ammonium fluoride, and titanium tetrafluoride; the vanadium source is one or more of vanadium pentoxide, vanadium oxysulfate, ammonium metavanadate, and vanadium trioxide; and the titanium source is one or more of titanium tetrachloride, titanium hydroxide, and titanium oxysulfate.

[0015] Furthermore, the surfactant is one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate, or a mixture of the two.

[0016] Furthermore, in step (1), the sodium source, phosphorus source and fluorine source are dissolved in 100 ml of deionized water in a stoichiometric ratio of 3:2:3.

[0017] Furthermore, in step (2), the vanadium source and the titanium source are dissolved in 100 ml of deionized water according to a stoichiometric ratio of 2-x:x.

[0018] Furthermore, in step (3) and step (4), stirring is performed at a speed of 300 r / min.

[0019] Furthermore, step (4) is heated in a water bath at 60° C. for 24 h.

[0020] Furthermore, the precipitate in step (5) and step (6) is separated by a centrifuge at a speed of 8000 r / min, and then washed with deionized water for 3 times and with alcohol for 3 times respectively. The washed product is placed in a drying oven and vacuum dried at 80° C. for 12 hours.

[0021] The NVPOF electrode material prepared by the above method is a micro-nano disc-shaped sodium vanadium oxyfluorophosphate positive electrode material formed by self-assembly of two-dimensional nanosheets along the z-axis. It has the advantages of uniform composition, uniform structure, high product purity, low energy consumption, and easy amplification. It has a capacity of 130.9 mAh g at 0.1C. -1 The initial high reversible capacity of the battery is 93.15%, which shows good reversibility. In addition, it has 125.68 mAh g at 1C. -1 The initial high reversible capacity and the capacity retention rate at 1C rate after 200 cycles were 70.14%, showing good cycling performance.

[0022] The battery prepared from the above materials has a positive electrode made of Na3V 2-x Ti x POF / C, Super P, and CMC are composed in a ratio of 7:2:1. The separator is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC in a mass ratio of 1:1, and the additive is FEC with a mass fraction of 2%. They are assembled into button batteries in an argon atmosphere, an oxygen-free and water-free glove box.

[0023] The beneficial effects of the present invention are:

[0024] (1) The industrialization of sodium-ion batteries is imminent. The co-precipitation method has a series of significant advantages over other methods (such as solid-phase method, solution-gel method, and spray-drying method) in the field of cathode material synthesis. These advantages are not only reflected in product quality and performance, but also in the efficiency and cost of the production process. The co-precipitation method can directly obtain products with uniform chemical composition. Uniform chemical composition can ensure the consistency and stability of the battery, which is especially important for battery cathode materials. In contrast, the solid-phase method often finds it difficult to achieve such fine control of chemical composition and particle size. Although the solution-gel method and spray-drying method can also prepare uniform materials, the process is more complicated and the cost is relatively high. In addition, the Na3V 2-x Ti x POF only requires a lower calcination temperature (400°C) and a shorter calcination time (5h), which helps save energy and further reduce production costs.

[0025] (2) Na3V synthesized by surfactant-assisted coprecipitation 2-x Tix In the process of POF materials, surfactants play a vital role in the design of NVPOF special morphology and the self-assembly of nanoparticles. Surfactants can help control the growth and aggregation of particles by reducing the interaction between nanoparticles, significantly changing the surface energy state of NVPOF nanoparticles and promoting their growth in a specific direction. This mechanism of action involves the adsorption behavior of surfactant molecules on the solid-liquid interface, which changes the interfacial free energy of the material, thereby guiding the nanoparticles to grow preferentially along a certain crystal plane to form a two-dimensional nanosheet structure and promote their accumulation along the z-axis direction, eventually forming a micro-nano disc structure. Its specific morphology and structural advantages are as follows: Na3V 2-x Ti x POF is composed of small disks with a diameter of about 1μm and a thickness of about 200nm, which are self-assembled by two-dimensional nanosheets along the z-axis. Its unique morphological characteristics can provide a higher specific surface area and more active sites for sodium ion embedding and de-embedding, thereby improving the specific capacity of the material. In such a structure of two-dimensional nanosheets self-assembled along the z-axis, electrons can move freely within the plane of the nanosheets, which is conducive to the rapid transmission of electrons. In addition, its close stacking along the z-axis can also provide a shorter transmission path for sodium ions. This is crucial to improving the inherent low electronic conductivity and slow ion diffusion rate of NVPOF.

[0026] (3) Based on the characteristics of dopamine self-aggregation on the surface of the material under weak alkaline conditions, we configured tris buffer to effectively maintain the pH value of the solution stable, which is crucial for the polymerization process of dopamine. After carbonization, the material coated with dopamine can form a uniform carbon layer with a thickness of about 5μm on the surface of the sample. This carbon layer can effectively inhibit the occurrence of secondary crystallization during the sintering process of the sample, thereby ensuring its original morphology. In addition, the carbon layer converted from dopamine after carbonization is a nitrogen-doped carbon layer, which can further improve the electronic conductivity of the material. Description of the drawings:

[0027] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0028] Figure 1 Figure 2 Figure 3 Ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared by surfactant-assisted synthesis in this application 2-x Ti x SEM images of POF / C sample and the final sample without adding surfactant;

[0029] Figure 4Ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared by surfactant-assisted synthesis in this application 2-x Ti x TEM image of POF / C material;

[0030] Figure 5 Ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared by surfactant-assisted synthesis in this application 2-x Ti x XRD pattern of POF / C material;

[0031] Figure 6 As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared by the present application using surfactant-assisted synthesis 2-x Ti x The charge and discharge curve of POF / C material at 0.1C;

[0032] Figure 7 The rate performance diagram of the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V2-xTixPOF / C material prepared by the surfactant-assisted synthesis in the present application;

[0033] Figure 8 Figure 7 Ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared by surfactant-assisted synthesis in this application 2-x Ti x 1C cycle performance diagram of POF / C material. Specific implementation method:

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, all raw materials in the following examples were commercially available.

[0036] Embodiment 1:

[0037] A method for synthesizing ion-doped and carbon-coated dual-modified NVPOF electrode materials using surfactants, comprising the following steps:

[0038] S1: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium citrate, and sodium fluoride; the vanadium source is one or more of vanadium pentoxide, vanadium oxysulfate, ammonium metavanadate, and vanadium trioxide; the titanium source is one or more of titanium tetrachloride, titanium hydroxide, and titanium oxysulfate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and disodium hydrogen phosphate; the fluorine source is one or more of sodium fluoride, ammonium fluoride, and titanium tetrafluoride.

[0039] S2: Dissolve the sodium source, phosphorus source and fluorine source in S1 in 100ml of deionized water at a stoichiometric ratio of 3:2:3, stir thoroughly until all the drugs are completely dissolved, and record it as solution A. Take another beaker, dissolve the vanadium source and titanium source in 100ml of deionized water at a stoichiometric ratio of 2-x:x, stir thoroughly until all the drugs are completely dissolved, and the solution color is bluish white, and record it as solution B. Transfer solution B to solution A with a plastic dropper, and stir at a speed of 300r / min. A large amount of white-gray floccules will be produced at the moment of dropwise addition. The mixed solution is recorded as solution C. At this time, add 2g of surfactant to solution C, stir thoroughly at a speed of 300r / min for 2h, and place the above solution in a water bath at 60℃, and heat it in a water bath at this temperature for 24h.

[0040] S3: At this time, the supernatant can be observed to be a colorless liquid, the white flocs in the beaker disappear and a blue-white precipitate is produced. The above product is washed with deionized water 3 times and alcohol 3 times at a speed of 8000r / min in a centrifuge, and the washed product is placed in a drying oven at 80°C for 12 hours under vacuum to obtain Na3V 2-x Ti x POF.

[0041] S4: The Na3V 2-x Ti x POF and 0.2 g of dopamine hydrochloride were dissolved in 200 ml of tris buffer and stirred thoroughly. The obtained product was washed with deionized water 3 times and alcohol 3 times at a speed of 8000 r / min by centrifuge. The washed product was placed in a drying oven and vacuum dried at 80 ° C for 12 h. The dried product was placed in a tubular furnace and calcined at 400 ° C for 5 h under argon atmosphere to obtain the final product Na3V 2-x Ti x POF / C.

[0042] S5: The positive electrode is made of Na3V 2-x Ti xPOF / C, Super P, and CMC are composed in a ratio of 7:2:1. The separator is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC (mass ratio 1:1), and the additive is 2% FEC by mass. The button battery is assembled in an argon atmosphere, an oxygen-free and water-free glove box.

[0043] Comparative Example:

[0044] No surfactant was added, and the other steps were the same as in Example 1.

[0045] Verification results:

[0046] like Figure 1 As shown in FIG. 1 , it is a SEM image of the final sample obtained in step (4) when no surfactant is added. The sample is composed of primary nanoparticles with a diameter of about 200-300 nm, and no self-assembly phenomenon occurs between the particles. Figure 2 Figure 3 As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared in step (4) using surfactant-assisted synthesis 2-x Ti x SEM image of POF / C material; it can be seen from the figure that the prepared Na3V 2-x Ti x POF particles are composed of small disks with a diameter of about 1μm and a thickness of about 200nm, which are self-assembled by two-dimensional nanosheets along the z-axis. The unique morphological characteristics can provide a higher specific surface area and more active sites for sodium ion embedding and de-embedding, thereby improving the specific capacity of the material. Such a structure of two-dimensional nanosheets self-assembled along the z-axis is conducive to the rapid transmission of electrons, because electrons can move freely in the plane of the nanosheets. In addition, its close stacking along the z-axis can also provide a shorter transmission path for sodium ions. This is crucial to improving the inherent low electronic conductivity and slow ion diffusion rate of NVPOF.

[0047] like Figure 4 As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared in step (4) using surfactant-assisted synthesis 2-x Ti x TEM image of POF / C material. First, we can clearly observe that the surface of the material is evenly covered with a carbon layer of about 5nm thick. This carbon layer is N-doped carbon obtained by carbonization of dopamine, which can effectively improve the low electronic conductivity of the material and inhibit the volume expansion of the material during the charge and discharge process. In addition, the clear lattice fringes confirm that the material has good crystallinity.

[0048] like Figure 5As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared in step (4) using surfactant-assisted synthesis 2-x Ti x XRD diagram of POF / C material. The data results show that the Na3V prepared by this method 2-x Ti x All the diffraction peaks of POF / C are in good agreement with those of Na3V2(PO4)2O2F (PDF#01-076-3645), which proves that the doping of titanium ions does not introduce new peaks and that the samples prepared by the coprecipitation method are pure and free of impurities.

[0049] like Figure 6 As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared in step (4) using surfactant-assisted synthesis 2-x Ti x The first cycle charge-discharge curve of POF / C material at 0.1C. From the charge-discharge curve of the sample between 2.0-4.3V, two pairs of obvious voltage platforms can be observed, located at about 3.7 and 4.1V, respectively. The redox peaks of 3.62 / 3.71V correspond to the insertion / deinsertion of Na2, and the redox peaks of 4.04 / 3.12V correspond to the insertion / extraction of Na1. The first cycle discharge capacity at 0.1C can reach about 130.9mAh / g, showing extremely excellent electrochemical performance.

[0050] like Figure 7 As shown in the figure, the ion-doped and carbon-coated double-modified sodium vanadium fluorophosphate Na3V prepared in step (4) using surfactant-assisted synthesis 2-x Ti x The rate characteristics of the electrodes of POF / C materials at current densities of 0.1 to 10C. When the current densities of 0.1C, 0.2C, 0.5C, 1C, 5C, and 10C are applied, the Na3V 2-x Ti x The discharge specific capacities of the POF / C positive electrode are 130.9Ah / g, 128.2mAh / g, 121.6mAh / g, 114.1mAh / g, 83.9mAh / g, and 55.4mAh / g, respectively. This proves that the sample has an excellent rate performance.

[0051] like Figure 8 As shown in step (4), the sodium vanadium fluorophosphate Na3V is prepared by ion doping and carbon coating double modification using surfactant-assisted synthesis. 2-x Ti x Cycling performance diagram of the electrode of POF / C material at 1C. At 1C, it has 125.68 mAh g -1The initial high reversible capacity and the capacity retention rate at 1C rate after 200 cycles were 70.14%, showing good cycling performance.

Claims

1. A method for synthesizing ion-doped and carbon-coated dual-modified NVPOF electrode materials using surfactants, characterized in that The following steps are involved: (1) Dissolve the sodium source, phosphorus source, and fluorine source in deionized water in proportion and stir thoroughly until each drug is completely dissolved to obtain a colorless solution, which is recorded as solution A; (2) Take a beaker and dissolve the vanadium source and titanium source in deionized water in proportion. Stir thoroughly until all the chemicals are completely dissolved to obtain a blue-white solution, which is recorded as solution B. Dissolve the vanadium source and titanium source in 100 ml of deionized water in a stoichiometric ratio of 2-x:x, where 0 <x<2; (3) Transfer solution B to solution A at a certain dropwise addition rate and stir at a certain speed. A large amount of white-gray floccules are produced at the moment of dropwise addition. The mixed solution is recorded as solution C. (4) Adding a surfactant to the C solution and stirring thoroughly, placing the solution in a water bath, heating the solution in a water bath, obtaining a colorless supernatant, and the white-gray floccules in the beaker disappear and a bluish-white precipitate is generated; the surfactant is one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate, or a mixture of the two; (5) After centrifugation, centrifuge with deionized water and alcohol three times and dry in a drying oven to obtain Na3V 2-x Ti x (PO4)2O2F, Na3V 2-x Ti x POF; (6) Na3V 2-x Ti x POF and dopamine hydrochloride were dissolved in tris buffer and stirred thoroughly. The obtained product was centrifuged and washed again and dried. The dried product was calcined in a tube furnace under argon atmosphere to obtain the final product Na3V 2-x Ti x (PO4)2O2F / C, i.e. Na3V 2-x Ti x POF / C.

2. The method according to claim 1, characterized in that: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium citrate, and sodium fluoride; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, and disodium hydrogen phosphate; the fluorine source is one or more of sodium fluoride, ammonium fluoride, and titanium tetrafluoride; the vanadium source is one or more of vanadium pentoxide, vanadium oxysulfate, ammonium metavanadate, and vanadium trioxide; and the titanium source is one or more of titanium tetrachloride, titanium hydroxide, and titanium oxysulfate.

3. The method according to claim 1, characterized in that: In step (3) and step (4), stirring is performed at a speed of 300 r / min.

4. The method according to claim 1, characterized in that: Step (4) was heated in a water bath at 60°C for 24 h.

5. The method according to claim 1, characterized in that: In step (5) and step (6), the precipitate is separated by a centrifuge at a speed of 8000 r / min, and then washed with deionized water for 3 times and with alcohol for 3 times respectively. The washed product is placed in a drying oven and vacuum dried at 80° C. for 12 h.

6. The NVPOF electrode material prepared by any method of claims 1-5, characterized in that: It is a micro-nano disc-shaped sodium vanadium fluorophosphate cathode material formed by self-assembly of two-dimensional nanosheets along the z-axis; it has a capacity of 130.9 mAh g at 0.1C. -1 The initial high reversible capacity of the battery can reach 93.15% with a first coulombic efficiency of 125.68 mAh g at 1C. -1 The initial high reversible capacity is 70.14% at 1C rate after 200 cycles.

7. A battery prepared from the material according to claim 6, characterized in that: The positive electrode is made of Na3V 2-x Ti x POF / C, Super P, and CMC are composed in a ratio of 7:2:

1. The separator is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC in a mass ratio of 1:1, and the additive is FEC with a mass fraction of 2%. They are assembled into button batteries in an argon atmosphere, an oxygen-free and water-free glove box.

Citation Information

Patent Citations

  • NaVPO4F / C composite material and preparation method thereof

    CN108199028A

  • Carbon-coated fluorine-containing electrode material Na3V2O2x(PO4)2F(3-2x) and preparation method thereof

    CN109473638A

  • Preparation method and application of high-specific-capacity transition metal doped carbon coated sodium vanadium fluorophosphate material

    CN116504964A